THE RELEVANCE OF PIERRE BOURDIEU’S THEORY IN THE CONTEXT OF CONTEMPORARY INDONESIAN SOCIETY - Abd. Fatah, Rahmat; Haji Noh, Muhammad; Djana, Amrul; Artha, Sarni (International Journal of Multidisciplinary Reseach, 2026)
Despite the extensive global influence of Pierre Bourdieu’s sociology, systematic analyses of the relevance and contextual application of his theoretical framework within contemporary Indonesian society remain limited. This study addresses this problem by examining how Bourdieu’s core concepts habitus, field, various forms of capital, and symbolic violence are utilized to explain social relations and power dynamics in Indonesia. The aim of this article is to assess the relevance and explanatory capacity of Bourdieu’s theory in Indonesian social research, particularly in the fields of education, gender relations, and state institutional practices. This study employs a qualitative research design based on a systematic literature review of open-access scholarly articles indexed in Dimensions.ai and Scopus-reputable publications accessed via Google Scholar. Data were analyzed thematically by identifying patterns in the application of Bourdieusian concepts across selected studies. The findings indicate that Bourdieu’s theoretical framework remains highly relevant for understanding social inequality, cultural domination, and symbolic forms of power in contemporary Indonesia. The study demonstrates that Bourdieu’s relational approach enables a nuanced analysis of how domination is reproduced through everyday practices, cultural norms, and institutional structures, thereby offering a critical lens for interpreting the multilayered complexities of Indonesian society.